THE U.S. NATIONAL SECURITY COUNCIL IN CONTEMPORARY AMERICAN INTERNATIONAL STUDIES - V. V. Pavlov (Vestnik MGIMO-Universiteta)
Established in accordance with the provisions of the National Security Act of 1947, the U.S. National Security Council is the main advisory body to the President of the United States tasked with helping the head of state to make the right decisions on matters related to national security. NSC system has been constantly evolving for some 70 years, and the NSC staff became a separate 'ministry' of a kind, allowing presidential administrations to focus ever-increasing control over American foreign policy in the White House. That is why serious attention is devoted to the National Security Council by American researches studying foreign policy decision-making. Here, a 'three-pronged consensus' exists: functioning and efficiency of the decision-making process is primarily a result of presidential actions; the President will make the best decision after becoming aware of the whole range of possible alternatives and assessing the consequences of each policy option; the position of the National Security Advisor, who is often one of the closest officials to the President and serves as a coordinator of the decision-making process, is considered to be one of the most notable in today's U.S. presidential administrations - and the most influential of those not being a subject to approval by the legislative branch of U.S. government. Any fundamental changes in the practice of U.S. foreign policy mechanism, as well as a decline of the White House influence on foreign policy are unlikely in the short term.